Detection of C2HD and the D/H ratio on Titan - Coustenis, Athena; Jennings, Donald E.; Jolly, Antoine; Bénilan, Yves; Nixon, Conor A.; Vinatier, Sandrine; Gautier, Daniel; Bjoraker, Gordon L.; Romani, Paul N.; Carlson, Ronald C.; Flasar, F. Michael (Icarus (New York, N.Y. 1962), 2008)
We report here the first detection of mono-deuterated acetylene (acetylene-d1, C 2HD) in Titan's atmosphere from the presence of two of its emission bands at 678 and 519 cm -1 as observed in CIRS spectral averages of nadir and limb observations taken between July 2004 and mid-2007. By using new laboratory spectra for this molecule, we were able to derive its abundance at different locations over Titan's disk. We find the C 2HD value ( 1.27-0.22-0.13×10) to be roughly constant with latitude from the South to about 45° N and then to increase slightly in the North, as is the case for C 2H 2. Fitting the 678 cm -1nu band simultaneously with the nearby C 2H 2 729 cm -1nu band, allows us to infer a D/H ratio in acetylene on Titan with an average of the modal values of 2.09±0.45×10 from the nadir observations, the uncertainties being mainly due to the vertical profile used for the fit of the acetylene band. Although still subject to significant uncertainty, this D/H ratio appears to be significantly larger than the one derived in methane from the CH 3D band (upper limit of 1.5×10; Bézard, B., Nixon, C.A., Kleiner, I., Jennings, D.E., 2007. Icarus, 191, 397-400; Coustenis, A., Achterberg, R., Conrath, B., Jennings, D., Marten, A., Gautier, D., Bjoraker, G., Nixon, C., Romani, P., Carlson, R., Flasar, M., Samuelson, R.E., Teanby, N., Irwin, P., Bézard, B., Orton, G., Kunde, V., Abbas, M., Courtin, R., Fouchet, Th., Hubert, A., Lellouch, E., Mondellini, J., Taylor, F.W., Vinatier, S., 2007. Icarus 189, 35-62). From the analysis of limb data we infer D/H values of 9.6-3.1-4.5×10 (at 54° S), 2.4-0.7-0.9×10 (at 15° S), 2.7-0.6-0.7×10 (at 54° N) and 1.9-0.5-0.7×10 (at 80° N), which average to a mean value of 1.63±0.27×10.